Lung Ventilation Modeling for Assessment of Lung Status: Detection of Lung Disease and Indication for Extubation of Mechanically-Ventilated COPD Patients - Ghista, Dhanjoo N.; Koh, Kah Meng; Pasam, Rohit; Su, Yi (IntechOpen, 2012)
None